The ionic conductivity and electrochemical performance of Alginate-PVA based polymer electrolyte with Li+ charge carriers for supercapacitor - Ahmad Salihin, Samsudin; Nuraziliana, Muhd Ghazali; Nor Fatihah, Mazuki; Aoki, Kentaro; Nagao, Yuki (Elsevier, 2024)
This study presents the synthesis and characterization of solid polymer blend electrolytes (SPBEs) using alginate (Alg) and polyvinyl alcohol (PVA) as host polymers, incorporating lithium bis(trimethanesulfonyl)imide (LiTFSI) as the ion-providing salt for potential application in EDLCs. The surface morphology of the SPBEs was revealed using scanning electron microscopy (SEM), while thermal gravimetric analysis (TGA) demonstrates enhanced thermal stability, characterized by reduced weight loss and a shift toward higher decomposition temperature. Complexation between Alg-PVA and LiTFSI was indicated by Fourier-transform infrared spectroscopy (FTIR), as evident by the transitions and intensity changes in FTIR bands corresponding to functional groups. Increasing LiTFSI content reduces bulk resistance, with Alg-PVA containing 20 wt% LiTFSI (Li-20) showing maximum room temperature ionic conductivity (3.31 × 10-4 S cm−1) and the lowest activation energy (0.05 eV). Transport properties, analyzed using the Arof-Noor (A-N) method, reveal that ionic conductivity in SPBEs is governed by ionic mobility and ions’ diffusion coefficient. Sample Li-20 displays predominantly ionic transport with a transference number (tion) 0.98 and electrochemical stability up to 2.55 V. The EDLC, employing activated carbon electrodes and the most conductive electrolyte, demonstrates notable performance features, including specific capacitance (87.51F/g at 2 mV/s, assessed from CV), energy density (25.17 Wh kg−1), and power density (1038.92 W kg−1). Testing at various current densities reveals the highest specific capacitance values associated with the lowest current density, measuring 51.15F/g for the EDLC cell based on the Li-20 sample.